2022
DOI: 10.33146/2307-9878-2022-2(96)-58-67
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cyber Threats and Technical Problems on Customer's Attitude Towards E-Banking Services

Abstract: The study showed the effect of cyber threats or technical problems on customer attitude towards e-banking services. A self-administered questionnaire was used to collect the data, and 400 respondents from eight divisions (Dhaka, Barisal, Rangpur, Chittagong, Khulna, Mymensingh, Rajshahi, and Sylhet) participated in the study. The researcher used a linear regression model to assess the relationship between dependent and independent variables. STATA and SPSS v. 25 program environment were used to conduct the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…More specifically, the framework argues that the three proposed drivers or stimuli of social media advertising (i.e., entertainment, interaction, and e-WOM) interact to both brand image and consumers' intention to purchase. This assertion is supported by similar studies in the field (Seo and Park, 2018;Işık et al, 2024a;Islam et al, 2022;Işık et al, 2024b;Dehghani et al, 2015;Islam et al, 2024;Bilgin, 2018;Algharabat, 2017;Rana et al, 2023;Islam et al, 2020;Godey et al, 2016;Islam et al, 2021). Within this context, Seo and Park (2018) and Bilgin (2018) found that entertainment and interaction significantly influence the brand image of products in social media advertising, and e-WOM also exerts a noteworthy impact on these components (Godey et al, 2016).…”
Section: Theoretical Background and Hypotheses Developmentsupporting
confidence: 53%
“…More specifically, the framework argues that the three proposed drivers or stimuli of social media advertising (i.e., entertainment, interaction, and e-WOM) interact to both brand image and consumers' intention to purchase. This assertion is supported by similar studies in the field (Seo and Park, 2018;Işık et al, 2024a;Islam et al, 2022;Işık et al, 2024b;Dehghani et al, 2015;Islam et al, 2024;Bilgin, 2018;Algharabat, 2017;Rana et al, 2023;Islam et al, 2020;Godey et al, 2016;Islam et al, 2021). Within this context, Seo and Park (2018) and Bilgin (2018) found that entertainment and interaction significantly influence the brand image of products in social media advertising, and e-WOM also exerts a noteworthy impact on these components (Godey et al, 2016).…”
Section: Theoretical Background and Hypotheses Developmentsupporting
confidence: 53%
“…User satisfaction is vital for the success of MFS, and technical issues have a direct impact on users' overall satisfaction with the services. Technical issues and challenges have a significant influence on users' attitudes toward MFS (Shin, 2009;Islam et al, 2022). Slow processing times, system faults and frequent interruptions hinder the smooth execution of financial operations, leading to lower levels of satisfaction (Lin, 2007).…”
Section: Purpose Of Use Of Mfs and Perception About Mfsmentioning
confidence: 99%
“…A variety of research on economic elements, some of them including macroeconomic variables, influence bank financial performance (Asif et al, 2023;Brahmaiah, 2018;Kirimi et al, 2020;Petria et al, 2015;Işık et al, 2021Işık et al, , 2024aIşık et al, , 2024bIşık et al, , 2024cIşık et al, , 2024d2024fIslam et al, 2024Mamun et al, 2022;Islam et al, 2020;Islam et al, 2022;Islam et al, 2023a;Islam et al, 2023b;Rana et al, 2023;Işık et al, 2024c;Işık et al, 2024dHasan et al, 2019Rahman, 2019). Inflation, gross domestic product (GDP), national income, per capita income, exchange rates, interest rates, unemployment levels, and financial crises are all macroeconomic factors that affect banks performance (Bhattarai, 2017;Cetin et al, 2023;Neupane, 2020;Ozatac et al, 2018;Saeed, 2014;Simiyu and Ngile, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%